Odnosi med spletnim trženjem od ust do ust, oglaševanjem in dimenzijami premoženja blagovne znamke - Konečnik Ruzzier, Maja (Teorija in praksa, 2022)
Marketing communication tools are not under the complete control of marketers in an interactive environment, making it important to know how they impact the brand equity creation process. The article studies the impact of electronic word-of-mouth and television advertising on dimensions of consumer-based brand equity and tests it on a sample of Slovenian consumers. Alongside the presented research confirming the important role of both communication tools, it shows the need for prudence in addressing separate brand equity dimensions. The results support upgrading the traditional communication mix with interactive tools that typically involve and stimulate consumers to co-create brands, yet not at the cost of neglecting traditional advertising.
Keywords: Blagovne znamke; internetno trženje; marketing; Oglaševanje; Trženje